MOS varactors with n- and p-type gates and their influence on an LC-VCO in digital CMOS. - Maget, J. (IEEE Journal of solid state circuits)
The influence of the gate doping type of the MOS varactor on frequency tuning, phase noise, and frequency sensitivity to supply-voltage variations of a fully integrated inductance-capacitance voltage-controlled oscillator (LC-VCO) is presented. Three varactors in multifinger layout with shallow trench isolation (STI) are compared. The polysilicon gate is either entirely n- or p-doped or the fingers have alternating n and p doping. Differences in capacitance and quality factor are shown. Two identical VCOs with the varactors having n gates or np gates are realized. Homogenous doping increases the VCO tuning range to 1.31 GHz (±20%) in comparison to 1.06 GHz (±15%) obtained by mixed doping. However, mixed doping has the advantages of more linear VCO frequency tuning, lower close-in phase noise, and reduced maximum sensitivity to variations in supply voltage. Several varactor parameters are introduced. They allow prediction of the influence of varactors on the performance of a given VCO. With a current consumption of only 1 mA from a supply voltage of 1.5 V, both VCOs show a phase noise of -115 dBc/Hz at 1-MHz offset from a 4-GHz carrier and a VCO figure of merit of -185.3 dBc/Hz.